Aerobic starvation treatment of activated sludge enhances the degradation efficiency of refractory organic compounds. (1st October 2022) - Sun, Haohao; Xia, Juntao; Wu, Bing; Ren, Hongqiang; Zhang, Xuxiang; Ye, Lin
Highlights: Bacterial community in activated sludge changes under aerobic starvation condition. Aerobic starvation improves degradation efficiency of some ROCs in activated sludge. Relative abundance of BPA degrading bacteria increases under starvation condition. Aerobic starvation can increase the expression of some ROC degrading genes. Abstract: Many refractory organic compounds (ROCs) in wastewater are toxic to human and aquatic organisms. Here, we reported an aerobic starvation approach to improve the degradation efficiencies of ROCs in activated sludge systems. The highest degradation rates of bisphenol AF (BPAF) (11.4 mg/g VSS · h) and gabapentin (GBP) (8.9 mg/g VSS · h) were achieved on the second day of the starvation process. While, the degradation rate of bisphenol A (BPA) on the 43rd day reached the maximum value of 0.8 mg/g VSS ·h, which was significantly higher than that of the seeding sludge (0.01 mg/g VSS · h). To investigate the mechanisms of this finding, we applied magnetic-nanoparticle mediated isolation, 16S rRNA gene sequencing, metagenomic sequencing and metatranscriptomic sequencing to analyze the microbial community structures and functions during the starvation process. The results showed that the increase of the BPA degradation ability was caused by the increase of the relative abundance of BPA degrading bacteria ( Sphingomonas, Achromobacter, etc.), while, the enhancement of BPAF and GBP degradation was attributed to the increase of the expression of ROC degrading genes. Overall, these results improve our understanding of the microbial ecology of starved activated sludge and provide useful information for the future development of ROC removal technologies. Graphical abstract: Image, graphical abstract